1974
DOI: 10.1111/j.1471-4159.1974.tb06890.x
|View full text |Cite
|
Sign up to set email alerts
|

ELEVATION OF CYCLIC GMP LEVELS IN CENTRAL NERVOUS SYSTEM BY EXCITATORY AND INHIBITORY AMINO ACIDS1

Abstract: Guanosine 3',5' cyclic monophosphate (cyclic GMP) levels in incubated slices of mouse cerebellum are increased 10-fold by glutamate and two-to three-fold by glycine or y-aminobutyric acid (GABA). Glutamate also produces a 10-fold increase in adenosine 3',5' cyclic monophosphate (cyclic AMP) in the same tissue. However, GABA decreases cyclic AMP levels 30-40 per cent, and glycine produces only a transient 50 per cent accumulation of this cyclic nucleotide. Theophylline slightly augments the accumulation of cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

1976
1976
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(55 citation statements)
references
References 10 publications
1
53
0
1
Order By: Relevance
“…Finally, it has been shown that calcium is important in the regulation of the intracellular level of guanosine 3':5'-cyclic monophosphate (cGMP) (40). In the cerebellum of mice it has been found that depolarizing agents such as veratridine and ouabain or an increase in extracellular potassium raise the level of cGMP only in the presence of extracellular calcium (41,42). These data are supported by experiments in the bovine superior cervical ganglion (43) …”
Section: Abstracrsupporting
confidence: 69%
“…Finally, it has been shown that calcium is important in the regulation of the intracellular level of guanosine 3':5'-cyclic monophosphate (cGMP) (40). In the cerebellum of mice it has been found that depolarizing agents such as veratridine and ouabain or an increase in extracellular potassium raise the level of cGMP only in the presence of extracellular calcium (41,42). These data are supported by experiments in the bovine superior cervical ganglion (43) …”
Section: Abstracrsupporting
confidence: 69%
“…The elevation of cGMP in all of the dark-adapted photoreceptor layers suggests that the cGMP elevation is related to some event or process that occurs throughout the cell. This might be the depolarization that occurs in the dark (13,14), since cellular depolarization has been shown to elevate cGMP in other central nervous tissue (15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
“…The present data suggest that the rise in cyclic AMP could be caused by/or after the release of intracellular catecholamine. Ferrendelli et al (26) observed an increase in both cyclic AMP and GMP levels after the release of intracellular substances in mouse cerebellum slices stimulated by depolarizing agents.…”
Section: Discussionmentioning
confidence: 99%